Four new species of the spider genus Nesticella Lehtinen & Saaristo, 1980 from Laos, Thailand and Myanmar and the first description of the male of Nesticella yui Wunderlich & Song, 1995 with a proposed new diagnostic character for the family Nesticidae Simon, 1894 (Arachnida, Araneae) - Grall, Elena; Jäger, Peter (Zootaxa, 2016)
During various expeditions to Laos between 2003 and 2012 and one expedition to Myanmar in 2014, spiders of the family Nesticidae were collected inside and outside of caves. This was the first time this family was encountered in Laos. All specimens belong to the genus Nesticella Lehtinen & Saaristo, 1980. Four species have been recognized as being new to science, which are described in this paper: Nesticella beccus n. sp. (male, female; LAOS: Bolikhamsay Province, Luang Prabang Province, Huaphan Province, Khammouan Province, THAILAND: Mae Hong Son Province), Nesticella laotica n. sp. (male, female; LAOS: Vientiane Province, Huaphan Province, Luang Prabang Province, Bolikhamsay Province), Nesticella foelixi n. sp. (male; LAOS: Bolikhamsay Province) and Nesticella michaliki n. sp. (male, female; MYANMAR: Chin State). The male of Nesticella yui Wunderlich & Song, 1995 is described for the first time and it is the first record for Laos. Results from a first micro-computed tomography analysis of a female copulatory organ for this genus are provided. This analysis proves that female Nesticella exhibit a complex functional receptaculum, which is highly complex within the genus. The presence of a special type of leg setae (pipette setae) in males is proposed as diagnostic for the family Nesticidae.